The Diabetic Retinopathy Clinical Research Network (DRCR.net) and Its Contributions to the Treatment of Diabetic Retinopathy - Sun, Jennifer K; Jampol, Lee M (Ophthalmic research, 2019)
Over the past two decades, the Diabetic Retinopathy Clinical Research Network (now known as the DRCR Retina Network) has contributed to multiple and substantial advances in the clinical care of diabetic eye disease. Network studies helped establish anti-vascular endothelial growth factor (VEGF) agents as an effective alternative to panretinal photocoagulation for eyes with proliferative diabetic retinopathy (PDR) and as first-line therapy for eyes with visual impairment for diabetic macular edema (DME), defined treatment algorithms for the use of intravitreal medications in these conditions, and provided critical data to understand how to better evaluate the diabetic eye using optical coherence tomography and other imaging modalities. Ongoing DRCR.net studies will address whether anti-VEGF therapy is effective at preventing vision-threatening complications in eyes with severe non-proliferative diabetic retinopathy, if photobiomodulation has a beneficial effect in eyes with DME, and whether initiation of DME treatment with bevacizumab and rescue with aflibercept can provide visual outcomes as good as those achieved with aflibercept alone. Future plans for the Network also include the expansion into non-diabetic eye disease in areas such as age-related macular degeneration.